Prevalence and associated risk factors for anaemia amongst pregnant women attending three antenatal clinics in Eswatini - Rumbidzai C. Dodzo; Ropo E. Ogunsakin; Themba G. Ginindza (AOSIS, 2022)
Background: Anaemia is a global health problem affecting about a third of the world's population. In pregnancy, it is a public health concern with consequences for mothers and infants, including maternal death and infant mortality. In low-income countries (LICs), 25% indirect maternal mortality and 30% neonatal deaths are due to anaemia in pregnancy. Aim: This study aimed to determine the prevalence and risks associated with anaemia amongst pregnant women attending antenatal clinic (ANC) in three health facilities in Eswatini. Setting: This study was conducted in three health facilities in Eswatini, namely Mankayane, Raleigh Fitkin Memorial (RFM) and Mbabane Hospital. Methods: This cross-sectional study used non-probability sampling in three hospitals of Eswatini, to select 550 pregnant women, aged 15-49 years. Data were collected from January to March 2021, using face-to-face interviews with a structured questionnaire. Logistic regression was used for statistical analysis. Results: A total of 550 pregnant women were included in the study. Anaemia prevalence amongst pregnant women was 43.1% with mild, moderate and severe cases of 21.3%; 21.1% and 0.7%, respectively. Prevalence was high amongst women aged 15-19 years (53.3%). Factors associated with anaemia included living in urban areas (odds ratio [OR]: 1.8; confidence interval [CI]: 1.19-2.72), having anaemia 6 months before pregnancy (OR: 4.64; CI: 1.15-18.71), and gestational age at first ANC: third trimester (OR = 10.42; CI: 4.27-25.4) and second trimester (OR: 1.62; CI: 1.02-2.60). Conclusion: Anaemia remains prevalent amongst pregnant women in Eswatini. A comprehensive anaemia prevention programme would be justified and could lower the country's burden of anaemia.